Photoluminescence Properties of Nanocrystalline Sr2SnO4:Ti4+ Synthesized by Sonochemical Method - FAILAMANI (NIM 10505023), FAINAN
Nanocrystalline luminescence material of Sr2SnO4:Ti4+ has been synthesized by sonochemical method. The obtained powder then received heating treatment at different temperature of 100, 400, 600, 800, 1000, and 1400oC for two hours. X-ray diffraction pattern indicated that heating at 100oC would result in the presence of Sr2Sn(OH)8 as the dominant phase. Meanwhile, heating at 400oC stabilize SrSnO3 structure. All of sample heated over 400oC consist of two phases, which are Sr2SnO4:Ti4+ with orthorhombic structure with space group Pccn and impurity phase of SrCO3 also with orthorhombic structure with space group Pmcn. From the X-ray diffractogram the grain size could be estimated and it is found on the range of 22-60 nm. The grain size increases as the heating temperature increased. Photoluminescence measurement showed that nanocrystalline Sr2SnO4:Ti4+ exhibit broad emission peak in at about 420-428 nm which belong to blue light region. Heating at higher temperature increases photoluminescence intensity of nanocrystalline Sr2SnO4:Ti4+. Blue emissions were caused by electronic transition from Ti4+ defect levels to valence band of host materials.